Introduction: climate, cocoa and trees - Olwig, M.F.; Asare, R.; Meilby, H.; Vaast, P.; Owusu, K. (Palgrave Macmillan, 2024)
Climate change is predicted to significantly reduce areas suit-able for the cultivation of cocoa, an important cash crop providing a livelihood to over six million smallholders in the humid tropics. Cocoa agroforestry shows potential to increase climate resilience while providing more stable incomes, enhancing biodiversity, supporting healthy ecosys-tems and reducing the pace at which farms expand into forested areas. Based on the multidisciplinary ‘Climate Smart Cocoa Systems for Ghana’ research project, this book investigates the case of the biophysical and socioeconomic sustainability of cocoa agroforestry in Ghana, the second largest producer of cocoa in the world. After a brief introduction to the research project, this introductory chapter reviews the literature on the links between climate change, farming and agroforestry, thereby situating the study within a wider context. It then presents an in-depth analysis of historical Ghanaian cocoa yields and climate data at both the national and regional levels to establish a foundation for understanding the new climate risks faced by cocoa farmers. The chapter concludes by providing an overview of the chapters that follow and introducing the overall argument that agroforestry can only successfully address climate change impacts on cocoa farming if location-specific biophysical and socioeconomic factors are considered.